Cerebrospinal fluid hypoxanthine and xanthine concentrations as indicators of metabolic damage due to raised intracranial pressure in hydrocephalic children. Issue 7 (July 1984) - Levin, S D; Brown, J K; Harkness, R A
Abstract : Intracranial pressure and cerebrospinal fluid hypoxanthine and xanthine concentrations were measured in hydrocephalic children with suspected raised intracranial pressure. There was a highly significant correlation between intracranial pressure and cerebrospinal fluid hypoxanthine and xanthine levels.